2016
DOI: 10.5604/01.3001.0009.5164
|View full text |Cite
|
Sign up to set email alerts
|

When a doctor becomes a patient, the unique expectations and behaviours in a disease: preliminary report

Abstract: Descriptions and interpretations of cases in which a doctor becomes a patient are rather marginal in the Polish and Western medical literature. Still, analysis of doctors’ behaviours when they become patients themselves seems interesting. The available research results suggest that doctors find it difficult to adopt the role of a patient and very often delay the process of diagnosis and therapy. A substantial number of them treat themselves and have problems with following therapeutic advice. There are particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This phenomenon is also reported in the medical literature, where several studies have reported that doctors who treat doctor‐patients may also experience difficulties negotiating and getting cooperation from doctor‐patients (Fox et al, 2009, 2010; Tarkowski et al, 2016). It has been suggested that doctor‐patients often ignore their treating doctor's advice, negotiate treatment plans with their treating doctors and expect individual therapy (Fox et al, 2009, 2010; Tarkowski et al, 2016), which can be challenging for treating doctors. Although no studies to date indicate that nurse‐patients ignore their caregiver's advice or are more likely to negotiate their treatment with their carers, it is possible that this may occur with some nurse‐patients too.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This phenomenon is also reported in the medical literature, where several studies have reported that doctors who treat doctor‐patients may also experience difficulties negotiating and getting cooperation from doctor‐patients (Fox et al, 2009, 2010; Tarkowski et al, 2016). It has been suggested that doctor‐patients often ignore their treating doctor's advice, negotiate treatment plans with their treating doctors and expect individual therapy (Fox et al, 2009, 2010; Tarkowski et al, 2016), which can be challenging for treating doctors. Although no studies to date indicate that nurse‐patients ignore their caregiver's advice or are more likely to negotiate their treatment with their carers, it is possible that this may occur with some nurse‐patients too.…”
Section: Discussionmentioning
confidence: 53%
“…Although no studies have directly reported caregivers experiences while caring for nurse-patients, two publications on nurse-patient experiences suggest that some caregivers may hold the stereotype that nurses can be demanding patients, expecting to receive a high standard of care quality and cause additional stress when caring for nursepatients (Anonymous, 2013;Duke & Connor, 2008). This phenomenon is also reported in the medical literature, where several studies have reported that doctors who treat doctor-patients may also experience difficulties negotiating and getting cooperation from doctor-patients (Fox et al, 2009(Fox et al, , 2010Tarkowski et al, 2016). It has been suggested…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation